Effect of pre-milking udder stimulation on milk parameters in crossbred cows - SHINDE, KULADIP PRAKASH (Indian Journal of Dairy Science, 2016)
The objective of this study was to find out the effect of pre-milking udder stimulation on milk parameters in crossbred cows. Eighteen apparently healthy cross bred cows were randomly selected and divided into three treatments groups (6 in each group) namely T1, T2 and T3 based on udder stimulation for one minute, two minutes and three minutes, respectively. Milk yield was significantly (p